2013
DOI: 10.1016/j.smim.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Complement inhibition in cancer therapy

Abstract: For decades, complement has been recognized as an effector arm of the immune system that contributes to the destruction of tumor cells. In fact, many therapeutic strategies have been proposed that are based on the intensification of complement-mediated responses against tumors. However, recent studies have challenged this paradigm by demonstrating a tumor-promoting role for complement. Cancer cells seem to be able to establish a convenient balance between complement activation and inhibition, taking advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 144 publications
3
92
1
Order By: Relevance
“…Furthermore, our findings indicate upregulation of genes related to complement (C4A, C4B, and SERPING1) in BM-MSC exposed to leukemia in vivo. Consistent with our data, it has been recently shown that cancer cells can activate complement and such activation can promote an immunosuppressive microenvironment, induce angiogenesis and activate cancer-related signaling pathways [reviewed in [67]]. In this chronic inflammationlike state that resembles "a wound that does not heal" [14], stromal cells accumulate certain types of cytokines, chemokines, growth factors, matrix remodeling proteases, and reactive oxygen species critically compromising tissue homeostasis and creating a tumor-supportive microenvironment [68].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our findings indicate upregulation of genes related to complement (C4A, C4B, and SERPING1) in BM-MSC exposed to leukemia in vivo. Consistent with our data, it has been recently shown that cancer cells can activate complement and such activation can promote an immunosuppressive microenvironment, induce angiogenesis and activate cancer-related signaling pathways [reviewed in [67]]. In this chronic inflammationlike state that resembles "a wound that does not heal" [14], stromal cells accumulate certain types of cytokines, chemokines, growth factors, matrix remodeling proteases, and reactive oxygen species critically compromising tissue homeostasis and creating a tumor-supportive microenvironment [68].…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that cancer cells establish a balance between complement activation and inhibition. 29 However, controversial and conflicting data on the complement system's tumor-promoting, 30,31 and inhibiting activities, 24 have been published, 2 and the mechanisms of complement-specific activities in the tumor microenvironment are still unclear and demands further study.…”
Section: Discussionmentioning
confidence: 99%
“…The main pathway involved in activation of complement inside tumors is unclear, and evidence supports activation of each complement pathway in malignant tumors (40). To make matters more complicated, cancer cell membrane-bound serine proteases can also cleave C5 and generate C5a without complement activation (41).…”
Section: Immune Function Of the Complement Systemmentioning
confidence: 99%